Changes in enterprise potential in a circular economy: A comparative analysis of EU countries in 2013 and 2020 - Paweł Dziekański; Łukasz Popławski; Martin Straka (Entrepreneurial Business and Economics Review (EBER), 2025)
Objective: The article aims to identify and assess the spatial disparity of entrepreneurship and its links to the circular economy (CE) at the EU country level and to identify the practical implications of these phenomena for economic and regional policies that support sustainable development. Research Design & Methods: We employed literature analysis and statistical analysis. We used the TOPSIS method to create synthetic measures. We collected the empirical data by the spatial distribution of EU countries (including Eastern Bloc countries). The results of the analysis were presented in 2013 and 2020 (this is linked to the two programming periods of EU funds). It allowed for capturing the dynamic aspects of the studied phenomena and controlling the phenomenon of deviations related to the cyclical changes occurring in the economy. Findings: Entrepreneurship is an important element of economic growth that impacts the social sphere, improves the quality of life, and creates new jobs. The interaction between entrepreneurship and the circular economy is multidimensional, highlighting the importance of both entrepreneurship and the circular economy. The research shows a positive change in both areas, both in terms of entrepreneurship, compared to earlier years. Depending on the country, the situation regarding entrepreneurship and the circular economy varied. Malta, the Czech Republic, and the Netherlands were in a better situation in the entrepreneurship aspect, while Italy, Spain, and Greece were in a weaker situation. In the case of the circular economy, countries with better performance included the Netherlands, Slovenia, and Italy, while Denmark, Portugal, and Greece were worse off. Poland experienced growth in the area of entrepreneurship, while the situation remained more stable in the area of the closed economy, which affected the country's position in the international ranking. Implications & Recommendations: The obtained measures depend on the number and type of variables adopted for the study. Authorities can use this knowledge to assess the effectiveness of the development instruments and policy tools used so far. The results of the clustering can be the beginning of further in-depth research to determine which variables have had a decisive impact on the process of transformation and changes in the entrepreneurship area. Further empirical research is needed on the implementation of the CE, the relationship with the variables of demography, the financial situation, and environmental changes, as well as their impact on changes in the area of entrepreneurship. Actions taken in this aspect must be based on analyses that facilitate comparisons and on current information necessary for effective action. Contribution & Value Added: The study makes international comparisons between the studied areas, i.e., entrepreneurship and CE. The value of the article is the set of variables and the results of the analysis presenting the indicated relationship in the EU countries, with an indication of the Eastern Bloc countries in 2013 and 2020. It is an important stimulus in the discussion on strengthening the effectiveness of CE implementation in the conditions of a country and its impact on entrepreneurship changes.
Keywords: E60; F63; L26; L31; Q01; 330; Entrepreneurship; development potential; circular economy; multidimensional approach; synthetic measure; CRITIC-TOPSIS method